1991
DOI: 10.1159/000186469
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and Long-Term Prognosis of Patients with Acute Poststreptococcal Glomerulonephritis

Abstract: The prognosis of acute poststreptococcal glomerulonephritis (APSGN) is still a matter of considerable debate. In an attempt to elucidate this controversy, the medium-term prognosis was evaluated in 40 patients 5–9 years after the onset of the disease, and the long-term prognosis in 88 patients 10–17 years after the onset of the disease. All were sporadic cases. In the medium-term follow-up study, abnormalities were revealed in 5.0% (2/40) of the patients. Hypertension and proteinuria were the only abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
(20 reference statements)
4
14
0
1
Order By: Relevance
“…The long-term prognosis in children is also excellent. [5][6][7][8][9] The prognosis of the disease may be not so favorable in patients with additional risk factors such as low birth weight, older age, hypertension, diabetes or preexisting kidney disease. [10][11][12][13] Analysis of the follow-up data in our series revealed that three children fully recovered.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term prognosis in children is also excellent. [5][6][7][8][9] The prognosis of the disease may be not so favorable in patients with additional risk factors such as low birth weight, older age, hypertension, diabetes or preexisting kidney disease. [10][11][12][13] Analysis of the follow-up data in our series revealed that three children fully recovered.…”
Section: Discussionmentioning
confidence: 99%
“…It has a variety of initial symptoms. Severe headaches are the most frequent complaint of patients [1][2][3][4][5][6][7][8]. These may be Cerebral vasculitis can be caused by an infectious or noninfectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of the noninfec tious causes are the following: systemic necrotizing vasculitides; vasculitis associated with collagen vascular dis ease; neurosarcoid vasculitis, and drug-abuse vasculitis. The incidence of vasculitis following APSGN is increas ing [2,4,6,8], Vasculitis involving the skin is becoming more well-documented [ 1,2,4. 6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MCD, PSGN and glomerular hematuria were not included in the analysis of loss of renal function since progression to chronic renal failure is rare in these patients [9, 10, 11]. Our patients with PSGN were in different stages of disease; 10 were in the acute phase (first 2 months after the onset of symptomatology), 12 in the recovery phase (usually more than 2 months after the onset of symptoms but still with urinary abnormalities) and 14 could be considered cured (absence of urinary abnormalities or only slight or intermittent hematuria).…”
Section: Methodsmentioning
confidence: 99%